Female sexual dysfunction: a review - Kaundal, Asmita; Renjhen, Prachi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Sexual health is an important aspect of human life and to maintain a healthy and happy sexual life a positive integration of physical, social as well and psychological domains is very important. Any alteration in any of these domains can lead to sexual dysfunction which can significantly affect the quality of life of a couple. Many couples live with the problem and suffer silently due to shyness, stigmas, and social norms related to the issue. Many times even the treating medical professionals also do not screen for the sexual issues due to inadequate knowledge and training related to sexual dysfunction further increasing the burden of the disorder which remain undiagnosed. Sexual dysfunction can affect both men and women. Since the sexual cycle is complex in women both diagnosing and treating the female sexual dysfunction can often be challenging. Routine screening, meticulous workup and multidisciplinary approach is usually required to diagnose and mange sexual disorders.